Growth and population parameters of Nile tilapia, Oreochromis niloticus (L.) in the open waters of Lake Victoria, Kenya. Issue 4 (December 2016) - Yongo, Edwine; Outa, Nicholas
Abstract: The Nile tilapia ( Oreochromis niloticus ) was introduced into Lake Victoria in the early 1950s and 1960s and has since become the dominant tilapiine in the lake. This study investigated the growth and population parameters of O. niloticus in Lake Victoria on the basis of length–frequency data collected during the period June 2014 and June 2015. The asymptotic length ( L ∞ ) had a mean (±SE) value of 46.24 ± 0.04 cm TL, growth curvature ( K ) of 0.69 ± 0.25 year −1, total mortality ( Z ) of 2.18 ± 0.80 year −1, a natural mortality ( M ) of 1.14 ± 0.28 year −1, a fishing mortality ( F ) of 1.05 ± 0.53 year −1, an exploitation rate ( E ) of 0.46 ± 0.08, a growth performance index (∅) of 3.14 ± 0.17 and a length at first capture ( L C 50 ) of 20.31 ± 0.40 cm TL. Comparing the results of this study with previous studies indicates the parameters K, Z and M have increased, whereas ∅, F, E and L C 50 have decreased. Changes in these parameters could be attributed to the existing high fishing capacity, and changing lake conditions. Thus, management measures should include continued restriction on illegal fishing methods and gears, such as the use of undersized gillnets (<5 in. mesh size) and beach seines. More attention also should be directed to the implementation of measures to control pollution of the lake from its various sources.